Effect of Protein and Carbohydrate Combined with Resistance Training on Muscular Adaptation - Santos, Priscila Carvalho [UNESP]; Libardi, Cleiton Augusto; Nóbrega, Sanmy Rocha; De Carvalho, Milena Barbon [UNESP]; Galan, Bryan Steve Martinez [UNESP]; De Freitas, Ellen Cristini [UNESP] (Thieme, 2021)
The purpose was to compare the effects of protein (whey protein) and carbohydrate supplementation and protein alone both combined with resistance training on muscle strength, muscle mass and total training volume progression in untrained young men. Resistance training was performed using the leg press and knee extension until concentric failure (8-12 repetition maximum), three times a week for eight weeks. Muscle strength and muscle cross-sectional area were assessed before and after training. Total training volume progression was calculated considering the first and eighth week. Seventeen men completed the study (protein and carbohydrate, n=9, age 23.44 ± 4.56 years, weight: 62.13±6.17 kg, height: 1.75±0.02 m, body mass index: 20.29±2.08 kg/m 2; protein, n=8, age 24.63±2.39 years, weight: 69.01±5.57 kg, height: 1.77±0.07 m; body mass index: 21.64±1.05 kg/m 2. Both protocols showed similar increases in muscle strength (effect size: protein and carbohydrate=1.28; protein=0.97; p<0.001), muscle cross sectional area (effect size: protein and carbohydrate=0.66; protein=0.47; p<0.001) and total training volume progression (effect size: protein and carbohydrate=2.68; protein=1.63; p<0.001) after training. No differences were found between groups p>0.05). Protein and carbohydrate supplementation combined with resistance training does not induce greater gains in muscle strength, hypertrophy and total training volume compared to resistance training combined with protein alone in untrained individuals.
Keywords: muscle cross-sectional area; resistance training; strength; supplementation; ultrasound; whey protein